2009
DOI: 10.1097/pec.0b013e3181b91ff0
|View full text |Cite
|
Sign up to set email alerts
|

Observation Option for Acute Otitis Media in the Emergency Department

Abstract: Our study demonstrates that the observation option as defined by the New York Otitis Project Committee can be safely implemented in the ED and prevented the administration of antibiotics in more than 70% of the patients in our group. This suggests that if the observation option became the standard of care for the treatment of AOM, antibiotic administration for this disease could be significantly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…We were unable to obtain data from nine eligible studies because of no response (n=6), researchers moving on (n=2), or no response after initial agreement (n=1). 50 51 52 53 54 55 56 57 58 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were unable to obtain data from nine eligible studies because of no response (n=6), researchers moving on (n=2), or no response after initial agreement (n=1). 50 51 52 53 54 55 56 57 58 …”
Section: Resultsmentioning
confidence: 99%
“…634353637383940414243444546474849 IPD were obtained from 13 studies (nine RCTs, four observational studies; table 1), totalling 55 682 participants. We were unable to obtain data from nine eligible studies because of no response (n=6), researchers moving on (n=2), or no response after initial agreement (n=1) 505152535455565758…”
Section: Resultsmentioning
confidence: 99%
“…Interventions with a significant effect on antibiotic reduction were guidelines and the wait-and-see prescription in acute otitis media (AOM). For this latter a significant reduction was found in four articles (three of them with moderate to high quality) ( 29 , 34 , 52 , 66 ).…”
Section: Resultsmentioning
confidence: 94%
“…Nine out of 27 studies on interventions for antibiotic prescription (32%) reported about rapid viral testing ( 22 , 24 , 25 , 27 , 33 , 40 , 58 , 62 , 64 ), four about delayed antibiotic prescription in acute otitis media ( 29 , 34 , 52 , 66 ), six about guideline/management strategies ( 20 , 21 , 41 , 53 , 59 , 68 ), four about laboratory tests ( 22 , 46 , 47 , 49 ) and five using other interventions (Table 4 ). In fourteen studies (50%) a significant reduction in antibiotic use was found.…”
Section: Resultsmentioning
confidence: 99%
“…Studies by other authors also demonstrate that wait-and-see approach to treatment of AOM in children is entirely acceptable. In one study Fischer T. and colleagues followedup 145 children with AOM that resolved spontaneously without any need for antibiotic treatment in 73% of cases [14], while in another study, Spiro D. M. and colleagues from USA followed-up 283 children and did not use any antibiotics in 62% of patients, but still achieved resolution of AOM [15]. The results of other studies are in accordance with the above data and suggest that spontaneous resolution within 7-14 days occurs in 70-90% of patients with AOM, in cases of first occurrence and sporadic AOM [16][17][18].…”
Section: Discussionmentioning
confidence: 98%